Drug Utilization Pattern in Osteoarthritis Patients at Porsea Regional Hospital - Togatorop, Baharuddin; Tamba, Rosanto; Pangaribuan, Daniel (Indonesian Journal of Science and Pharmacy, 2026)
Osteoarthritis (OA) is a degenerative joint disease that causes chronic pain and functional limitations, particularly in elderly populations. This study aimed to describe the pattern of drug utilization in OA patients at Porsea Regional General Hospital. This descriptive observational study used a retrospective approach based on outpatient and emergency medical records from March to May 2025. A total of 75 patient cases were selected using stratified random sampling. Variables analyzed included patient characteristics, comorbidities, types and classes of OA drugs, concomitant medications, and polypharmacy categories. The results showed that most patients were female (73.34%) and aged ≥60 years (65.53%). The majority had comorbidities (90.67%), with one to three conditions. The most frequently used OA drugs were non-selective NSAIDs, particularly diclofenac sodium (54.67%), followed by COX-2 selective inhibitors (meloxicam, 45.33%), paracetamol (10.67%), and opioid combinations (tramadol-paracetamol, 4.00%). Concomitant medications included vitamins/supplements (90.67%) and gastrointestinal drugs (85.33%). Major polypharmacy was observed in 81.33% of patients. In conclusion, OA patients were predominantly elderly women with high comorbidity and polypharmacy rates, and treatment was mainly dominated by NSAIDs.